2014
DOI: 10.1007/s00705-014-1977-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bovine torovirus in fecal specimens from calves with diarrhea in Turkey

Abstract: Bovine torovirus (BToV), a member of the family Coronaviridae, is an established gastrointestinal infectious agent in cattle. In this study, we performed a survey to detect BToV in Turkey between 2009 and 2011 using 235 fecal samples from neonatal calves with diarrhea that were analyzed by the nested reverse transcription (RT) PCR method using primers located in the consensus sequences of the BToV membrane (M) gene. The BToV M gene was detected in 4.7 % (11/235) of the samples using the nested RT-PCR method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
5
1
7
Order By: Relevance
“…The percentage of BToV infection found in this study (1.74%) is comparatively lower than that reported in other studies: 2.9% in South Korea [ 22 ], 4.7% in Turkey [ 24 ], 5.2% in Austria [ 19 ], 6.25% in Brazil [ 23 ], 8.4% in Japan [ 21 ], 9.7% in the USA [ 18 ], 36.4% in Canada [ 4 ], and 43.2% in Croatia [ 26 ]. Despite these differences, one cannot make a reliable comparison among these percentages because of the limited sample size used in the present and previous studies.…”
Section: Discussioncontrasting
confidence: 85%
“…The percentage of BToV infection found in this study (1.74%) is comparatively lower than that reported in other studies: 2.9% in South Korea [ 22 ], 4.7% in Turkey [ 24 ], 5.2% in Austria [ 19 ], 6.25% in Brazil [ 23 ], 8.4% in Japan [ 21 ], 9.7% in the USA [ 18 ], 36.4% in Canada [ 4 ], and 43.2% in Croatia [ 26 ]. Despite these differences, one cannot make a reliable comparison among these percentages because of the limited sample size used in the present and previous studies.…”
Section: Discussioncontrasting
confidence: 85%
“…Rotavirus is the main viral causative agent of diarrhea in calves worldwide [6]. However, several other viruses, including coronavirus, bovine viral diarrhea virus (BVDV), adenovirus, kobuvirus, norovirus, parvovirus, and torovirus, have been recognized as the causative agents of diarrhea [378910111213]. The major causative agents of bacterial diarrhea are Escherichia coli , Clostridium species (spp.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the HE gene sequences, BTOV can be divided into three genotypes [18]. In this study, a phylogenetic tree constructed using all 18 complete HE gene sequences available in the GenBank database showed that the two HE sequences belonged to a genotype that is prevalent throughout the world [10,12,25,37]. The torovirus HE protein contains three domains: MP, E and R, among which the R domain is involved in receptor recognition and plays an important role in the process of BToV infection [38].…”
Section: Discussionmentioning
confidence: 86%
“…The virus can not only be detected in feces but also in the respiratory tract, indicating that the virus has dual tissue tropism [6][7][8][9]. BToV has been detected in 16 countries with a wide geographical distribution [2,7,[10][11][12][13][14][15][16][17][18][19]. In addition, a sequence reported to be from goat torovirus is present in the GenBank database, and in 2012, researchers detected the presence of PToV in pig herds by RT-PCR in China [20].…”
Section: Introductionmentioning
confidence: 99%